The pursuit of new product development : the business development process - Annacchino, Marc A. (Butterworth-Heinemann, 2007)
Product Development begins with an understanding of market needs, within a sound business model, a well-defined financial strategy, and well-thought-out strategic goals. This new book by industry-expert Marc Annacchino, will help the professional engineer, manager, marketer, and all others who must come together as a working team, to better understand their respective roles and responsibilities in that process. Today, speeding the right value proposition to the market can make all the difference between success and failure. With case examples, organizational analysis and project planning tools, this new book looks at that longer, organizational view of product development, and how that view can improve product development cycle times and better take advantage of new market opportunities. It will help the product development team better adapt to change and a dynamic market in todays global economy through product platform management, and do so rationally and reliably. And it will help product development professionals to look for hidden value in existing product lines as they plan for that change and growth ahead. Provides product development professionals with the concepts and tools for a more integrated, successful product development cycle Promotes a more coherent deployment of managers, engineers, marketers, and sales personnel to achieve results within market opportunity in terms of time, cost and performance. Shows how to better identify and target product value propositions in product line extensions and in securing new markets.